2011
DOI: 10.1080/13504509.2011.576711
|View full text |Cite
|
Sign up to set email alerts
|

Common ground and shared frontiers in heritage conservation and sustainable development: partnerships, policies and perspectives

Abstract: Heritage conservation and sustainable development share common ground that is not being fully explored by design and planning professionals. This paper examines how innovators in both fields are seeking that common ground by challenging divided approaches to natural and cultural conservation, environmental and economic processes and the treatment of tangible and intangible resources. These divisions are reinforced by traditional institutional and educational structures, as well as polarised worldviews. Creativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 7 publications
0
3
0
1
Order By: Relevance
“…Ello va a exigir un gran pacto a nivel planetario que permita encontrar sinergias positivas entre los territorios. Se ha de trascender la rigidez del artefacto aislado de la ciudad y generar lugares colectivos cada vez más sostenibles, cohesionados e inclusivos (Pollock ellwand, 2011). La clave es que la población sea capaz de entender lo que la ciudad necesita y que la mayoría de los ciudadanos identifiquen el escenario de futuro que se desean.…”
Section: Creditos De Las Imágenesunclassified
“…Ello va a exigir un gran pacto a nivel planetario que permita encontrar sinergias positivas entre los territorios. Se ha de trascender la rigidez del artefacto aislado de la ciudad y generar lugares colectivos cada vez más sostenibles, cohesionados e inclusivos (Pollock ellwand, 2011). La clave es que la población sea capaz de entender lo que la ciudad necesita y que la mayoría de los ciudadanos identifiquen el escenario de futuro que se desean.…”
Section: Creditos De Las Imágenesunclassified
“…The joint nature of the JPs themselves, defined and implemented by UN agencies with different mandates, encouraged the implementation of integrated and coordinated strategies, sometimes being the first of this kind in these countries (Rajab 2013, 21). Considering the close interconnection between natural and cultural heritage and their communities, actions for environmental sustainability must adopt a holistic approach, encompassing not only ecological aspects, but also social, economic, and cultural dimensions (Keitumetse 2011;Pollock-Ellwand 2011). However, our analysis showed that the JPs mostly focused on the achievement of poverty alleviation, rather than gender equality and environmental sustainability, leading to the latter's marginalisation (Beasca 2011, 15;Bajeddi and Lahbil Tagemouati 2012, 10;Baltà Portolés 2013, 29).…”
Section: Enhancing Environmental Protection?mentioning
confidence: 99%
“…Such a network of articulations must transcend the rigidity of isolated artifacts such as buildings or cities and generate more and more sustainable, cohesive and inclusive collective places [120], as environments for cooperation and coexistence between dwellings and their surroundings whose purpose is to respond to the needs of the population, but also to the maintenance of biodiversity, which is crucial in the fight against future pandemics.…”
Section: Natural Environmentmentioning
confidence: 99%